2022
DOI: 10.29040/ijcis.v3i1.65
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Using E-Learning as an Online Learning Media at Polytechnic Indonusa Surakarta

Abstract: The Covid-19 outbreak has had a tremendous effect in no time. The Minister of Education and Culture of the Republic of Indonesia has adopted a policy to protect the nation's children from studying at home by means of distance education. Various technology platforms can be used to assist in the learning process. PJJ is e-learning-based learning. Indonusa Surakarta Polytechnic seeks to improve campus e-learning performance. To increase the use of e-learning, it is necessary to evaluate the use of campus E-Learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…Next, a research article also stated that e-learning was effectively applied as online learning during the COVID-19 pandemic. Based on this research, it is stated that e-learning is categorized as effective based on several categories [20]. These categories is illustrate through the following figure: Based on several research results from the article, it is concluded that elearning can and is appropriate to be used as a learning media in online learning, especially for high school level.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Next, a research article also stated that e-learning was effectively applied as online learning during the COVID-19 pandemic. Based on this research, it is stated that e-learning is categorized as effective based on several categories [20]. These categories is illustrate through the following figure: Based on several research results from the article, it is concluded that elearning can and is appropriate to be used as a learning media in online learning, especially for high school level.…”
Section: Resultsmentioning
confidence: 91%
“…Next, a research article also stated that e-learning was effectively applied as online learning during the COVID-19 pandemic. Based on this research, it is stated that e-learning is categorized as effective based on several categories[20]. These categories is illustrate through the following figure:…”
mentioning
confidence: 99%
“…This can support two-way communication and interaction between students and lecturers. The same thing was stated that the use of e-learning in universities is an innovation that can provide opportunities for lecturers to increase competence in designing digital learning and implementing learning according to the characteristics of students so that it can be more easily understood [16,17].…”
Section: Resultsmentioning
confidence: 99%
“…Sedangkan untuk penerapan dilapangan seperti di area komunitas, e-book juga mampu meningkatkan perhatian mahasiswa, motivasi, partisipasi, dan kepuasan mereka (Alifariki et al, 2023;Purwandari & Susena, 2022).…”
Section: Pembahasanunclassified